Effectiveness of ADI-based student worksheets on students’ argumentation skills in chemical equilibrium: A pre-experimental study - Adinda Nuriska Ragil Kinanthi; Utiya Azizah (Journal of Environment and Sustainability Education, 2025)
This study aims to describe the profile of students' argumentation skills on chemical equilibrium material through the use of student worksheets based on the Argument Driven Inquiry (ADI) learning model. The method used is a Pre-Experimental One Group Pretest-Posttest Design. This research method was applied to 29 grade XI students. The data collection method used is a test method with a pretest-posttest sheet instrument for argumentation skills. The results of the study showed an increase in students' argumentation skills on chemical equilibrium material after using student worksheets based on the ADI learning model. This was reviewed based on the n-gain score obtained in argumentation skills for the claim indicator of 1.00, the data indicator of 0.75, the warrant indicator of 0.77, and the backing indicator of 0.81, all n-gain scores on the four indicators were classified as high. In addition, this was also supported by an increase in the percentage of pretest-posttest argumentation skills and the results of the Wilcoxon test which showed an Asymp. Sig. (2-tailed) value of 0.000 <0.05 which indicated a significant difference between the pretest and posttest scores of students' argumentation skills. Based on these results, it can be concluded that there are significant differences and improvements in students' argumentation skills after using student worksheets based on the ADI learning model.